Impact of changing educational policies due to COVID-19 on the role of school principals in Dubai - MOUSSA, TAREK MAHMOUD (2020)
Keeping in view the fact that COVID-19 has transformed the education system, current study intends to explore the attitude of principals and administrators towards educational reforms and their upgradation in reference to crisis in educational sector. Moreover, the study also explored the role of principals and administration in effective implementation of educational reforms at the time of crisis. The relationship between the positive school performance, educational reforms, and significance of principals and administration in this regard was also scrutinized. To achieve the objective of the study mixed-method research design was employed where quantitative data were collected through questionnaire based survey and qualitative data were collected through interviews. The sample of the study was principals, leaders, and administrative unit in educational institutes of Dubai. The results of the study revealed that educational reforms are direly needed to deal with the issues occurred in educational system as a result of shifting to online educational system. Moreover, results also revealed that educational reforms need to be updated keeping in view the external circumstances that are quite novel in nature. Findings of the study supported the notion that principals and administration are the better position to mitigate the adversities caused by COVID-19 in educational sector. School performance and effectiveness of educational reforms were significantly positively related with the positive performance of the principals and administrators. The main limitation of the study is that the sample size is not the true representative of the targeted population and also the instruments used were not validated. In future, sequential mixed-method research design is suggested to employ in scrutinizing the educational reforms in context of Hybrid education system. Future studies should focus on formulating educational reforms in reference to hybrid education system and attitude of principals and administration towards it should also be explored.